Analisis Bibliometrik Penggunaan Video Pembelajaran di Sekolah Dasar Tahun 2013-2022 Menggunakan Aplikasi VOSViewer - Fitri Indriyanti; Tia Nurul Fauziah; Asep Nuryadin (Jurnal Educatio FKIP UNMA, 2023)
This study aims to analyze the use of instructional videos in elementary schools between 2013 and 2022 using the bibliometric computational mapping analysis method. The Publish or Perish software was used to collect publications data from the Google Scholar database using the keywords "Instructional Video" AND "Elementary School" OR "ES". This search yielded 282 articles. These results indicated that the number of publications related to this topic from 2013-2022 was still small, with an average number of publications of 28.2. Then, it was found that the highest number of publications was in 2021, with a total of 102 articles, while the lowest one was in 2014, with three articles. Analysis of the co-occurrence of keywords using VOSViewer resulted in 15 terms grouped into 5 clusters. Network and density visualization showed several keywords that often appear, namely, Elementary School (ES), instructional video, and video. In addition, the overlay visualization depicted keywords that have become a trend in recent years, namely, video, instructional media, animated video, mathematics learning, and teacher. Thus, future research needs to focus on various types of instructional videos and various subjects in elementary schools. Keywords: Bibliometric Analysis, Computational Mapping Analysis, Instructional Video, Elementary School, VOSViewer